EXPERIMENTAL PROCEDURE TO DETECT MULTIDOMAIN REMANENCE DURING THELLIER-THELLIER EXPERIMENTS - Krása D.; Heunemann C.; Leonhardt R.; Petersen N. (My University, 2003)
Reliability checks in Thellier-type experiments usually focus on the detection of chemical alteration of the magnetic mineral component or the formation of new magnetic phases during the heating process. However, a major problem in Thellier-type experiments is the presence of multidomain (MD) particles which can lead either to complete failure of palaeointensity determinations or to serious misinterpretation.We present a modification of the Thellier–Thellier experiment that detects the presence of MD particles by verifying the law of additivity of pTRMs. The law of additivity is valid for regular pTRMs (i.e. the upper temperature of pTRM acquisition is reached by cooling from the Curie temperature) for both SD and MD particles, whereas it is not valid for pTRM* (the upper temperature of pTRM acquisition is reached by heating from room temperature) in the case of MD particles. As the partial thermoremanences imparted in Thellier–Thellier experiments are of the pTRM* type, additivity as a prerequisite for the validity of the obtained result is not given if the remanence is carried predominantly by MD particles.The proposed method is applied to seven synthetic samples covering a grain size range of 23 nm to 12.1 μm. The obtained palaeointensity estimates show a significant error for all samples with grain sizes >0.7 μm due to the failure of the law of additivity. Our experiment is able to detect this failure.